2010
DOI: 10.1364/oe.18.025928
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nonlinear optical responses in donor-acceptor ionic complexes via photo induced energy transfer

Abstract: By complexion of donor and acceptor using ionic interactions, the enhanced nonlinear optical responses of donor-acceptor ionic complexes in aqueous solution were studied with 7-ns laser pulses at 532 nm. The optical limiting performance of negatively charged gold nanoparticles or graphene oxide (Acceptor) was shown to be improved significantly when they were mixed with water-soluble, positively-charged porphyrin (Donor) derivative. In contrast, no enhancement was observed when mixing with negatively-charged po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…In addition, these complex micelles also caused strong fluorescence quenching (Figure 4b). It has been reported that AuNPs are excellent electron/energy acceptors while porphyrins are superior electron/energy donors [28,29,30]. Thus, the energy transfer or electron transfer could occur from ZnTPPS to AuNPs, and the quench of fluorescence may indirectly demonstrate that such interactions took place between the gold and porphyrin in the micellar core.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these complex micelles also caused strong fluorescence quenching (Figure 4b). It has been reported that AuNPs are excellent electron/energy acceptors while porphyrins are superior electron/energy donors [28,29,30]. Thus, the energy transfer or electron transfer could occur from ZnTPPS to AuNPs, and the quench of fluorescence may indirectly demonstrate that such interactions took place between the gold and porphyrin in the micellar core.…”
Section: Resultsmentioning
confidence: 99%
“…An energy transfer model based on the graphene-porphyrin hybrids was developed and verified that the energy transfer from porphyrin to graphene enhances the TPA of the system. The role of energy transfer in the graphene based NLO materials was investigated by Mamidala et al, who blended the electron acceptor GO with positively charged porphyrin and negatively charged porphyrin, respectively (Mamidala et al 2010). The NLO response of the positively charged porphyrin-GO system is much larger than that of the negatively charged porphyrin-GO system, confirming the important role of the energy transfer in such donor-acceptor complexes.…”
Section: Organic Molecule Functionalized Graphene Compositesmentioning
confidence: 98%
“…Balapanuru et al [57] synthesized a GO-dye charge-transfer complex using a simple ionexchange process, and found that this GO-organic dye charge-transfer complex exhibited enhanced properties for biosensing and optical limiting. Mamidala et al [58] reported the enhanced NLO responses of donor-acceptor ionic complexes in aqueous solutions. The optical limiting performance of a negatively charged GO (acceptor) was shown to improve significantly when it was mixed with a water-soluble, positively-charged porphyrin (donor) derivative because of enhanced nonlinear scattering.…”
Section: Optical Limitingmentioning
confidence: 99%